2021
DOI: 10.1177/10778012211024267
|View full text |Cite
|
Sign up to set email alerts
|

“I’d Go from a Mountain Top and Tell My Story”: Perspectives of Survivors of Intimate Partner Violence on Storytelling for Social Change

Abstract: Storytelling has well-documented therapeutic benefits for survivors of trauma. However, little is known about intimate partner violence (IPV) survivors’ perspectives on sharing their stories. This article presents findings based on the analysis of 26 qualitative interviews with individuals who had experienced IPV regarding first-person story sharing. Participants described telling their stories as an act of healing and empowerment. They also named ways that storytelling can challenge societal views and structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Listening to the voices of both reporters and nonreporters, we provided insight into possible improvement of current SA report practices. Similar to the systemic perspective seen in the narratives of survivors of intimate partner violence (Dichter et al, 2022), the voices of the SA survivors in our study highlighted the interconnectedness between survivors and SART members, social institutions/organizations, and the larger society. When positive changes occur at all levels, survivors will be more likely to report their assaults and stay engaged in the reporting process.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Listening to the voices of both reporters and nonreporters, we provided insight into possible improvement of current SA report practices. Similar to the systemic perspective seen in the narratives of survivors of intimate partner violence (Dichter et al, 2022), the voices of the SA survivors in our study highlighted the interconnectedness between survivors and SART members, social institutions/organizations, and the larger society. When positive changes occur at all levels, survivors will be more likely to report their assaults and stay engaged in the reporting process.…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, we believed it was important to assess previously collected survivors’ experiences to determine additional recommendations to enhance these survivor-centered approaches. Past research has shown storytelling to be a powerful tool for survivors of intimate partner violence because it fosters empowerment and social change (Dichter et al, 2022). Additionally, researchers have demonstrated the power of stepping out of silence and shame by highlighting how storytelling transformed survivors into proactive SA advocates as they regained power and freedom and moved further through their healing process (Strauss Swanson & Szymanski, 2021).…”
Section: A Survivor-centered Approach In the Criminal Justice Systemmentioning
confidence: 99%
“…For Charon (2006), the author of Narrative Medicine, the telling of pain and suffering, and being heard and validated, enables people to give voice and frame to their experiences of illness, in order to escape its dominion over their lives. Research in trauma and violence has confirmed that these theoretical tenets can be applied outside of illness contexts and showed that supportive factors that contributed to a positive storytelling experience included the presence of a sympathetic, non-judgemental listener, and a supportive social environment (Dichter et al, 2022;Infusino, 2014;Mannell et al, 2018).…”
Section: Figure 2 Summary Of the Narrative Shelter Modelmentioning
confidence: 98%
“…Therefore, sharing their stories, being heard, and being taken seriously have emerged as contributing factors to fostering resilience in children and YP exposed to domestic and family violence (Callaghan et al, 2019;Fellin et al, 2019;Grover, 2005;Hines, 2015). However, no specific model has been developed to promote storytelling for YP with CEIPV as it exists for adult IPV survivors (Crann & Barata, 2021;Delker et al, 2020;Dichter et al, 2022;Wilson & Goodman, 2021;Wood, 2017). Focusing on this young age group has multiple implications for preventing and addressing potential cumulative victimization and enhancing cumulative resilience for the next generation of adults committed to preventing IPV.…”
Section: Storytelling and Storylistening In Fostering Resilience For ...mentioning
confidence: 99%
See 1 more Smart Citation